Analyzing the occurrence transformative learning in faith-based, postsecondary adult degree completion programs utilizing the learning activities survey - Mokhtarian, Kevin H. (Kansas State University, 2020)
There has been tremendous growth in adult, degree-completion programs. Enrollment trends continue to reflect a growing adult population, comprising 40% of all postsecondary students (Snyder & Dillow, 2013). In an effort to meet rising demand and capitalize on the opportunity to provide adult-specific programs, schools are focusing more on the administrative benefits and the highly structured format of degree completion programs and diminishing the opportunity for adults to learn and grow beyond course content (Johnson-Bailey, 2015). This ex-post facto study is of adult students enrolled in cohort-based, degree completion programs in faith-based colleges and universities to understand whether students experience transformative learning and if so, if their experience can be predicted or explained by participation in various learning activities. This research uses King’s (2009) Learning Activities Survey, which was specifically developed to measure transformative learning in the classroom. The purpose of this study, using the LAS, is to understand whether adult students in cohort-based, degree completion programs experience transformative learning and if it can be associated with learning activities. Students were surveyed and asked to report whether they experienced transformative learning in their educational program, outside of their experience in the program, or not at all.
Keywords: Adult education; Transformative learning; Mezirow; Degree completion; Cohort; Adult student